Perspective on the State of Pharmacometrics and Systems Pharmacology Integration. (21st August 2018) - Trame, Mirjam N.; Riggs, Matthew; Biliouris, Konstantinos; Marathe, Dhananjay; Mettetal, Jerome; Post, Teun M.; Rizk, Matthew L.; Visser, Sandra A. G.; Musante, Cynthia J.
Abstract : Reliance on modeling and simulation in drug discovery and development has dramatically increased over the past decade. Two disciplines at the forefront of this activity, pharmacometrics and systems pharmacology (SP), emerged independently from different fields; consequently, a perception exists that only few examples integrate these approaches. Herein, we review the state of pharmacometrics and SP integration and describe benefits of combining these approaches in a model‐informed drug discovery and development framework.